2003
DOI: 10.1021/jm0300476
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Cytotoxic 11-Alkenylindenoisoquinoline Topoisomerase I Inhibitors and Indenoisoquinoline−Camptothecin Hybrids

Abstract: The indenoisoquinolines are a novel class of topoisomerase I (top1) inhibitors that are cytotoxic in cancer cell cultures and are therefore under development as potential anticancer agents. As inhibitors of the DNA religation reaction occurring after DNA cleavage by the enzyme, they are classified as top1 poisons, similar to the camptothecins. Two strategies were employed in order to further develop the structure-activity relationships of the indenoisoquinolines and enhance their therapeutic potential. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 21 publications
(53 reference statements)
1
99
1
Order By: Relevance
“…Non-CPT Top1 inhibitors such as the indolocarbazoles NB-506 and J-107088 are in clinical trials (Meng et al, 2003). More recently, indenoisoquinolines and minor groove binders (benzimidazoles) have been reported to be promising Top1 inhibitors (Strumberg et al, 1999;Cushman et al, 2000;Rangarajan et al, 2000;Jayaraman et al, 2002;Fox et al, 2003;Nagarajan et al, 2003). Preliminary screening of approximately 100 derivatives of our parent indenoisoquinoline compound NSC 314622 has identified MJ-III-65 (NSC 706744) to be a potent inhibitor of purified Top1 in biochemical assay (Cushman et al, 2000;Antony et al, (Ross et al, 1979;Kohn, 1991 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-CPT Top1 inhibitors such as the indolocarbazoles NB-506 and J-107088 are in clinical trials (Meng et al, 2003). More recently, indenoisoquinolines and minor groove binders (benzimidazoles) have been reported to be promising Top1 inhibitors (Strumberg et al, 1999;Cushman et al, 2000;Rangarajan et al, 2000;Jayaraman et al, 2002;Fox et al, 2003;Nagarajan et al, 2003). Preliminary screening of approximately 100 derivatives of our parent indenoisoquinoline compound NSC 314622 has identified MJ-III-65 (NSC 706744) to be a potent inhibitor of purified Top1 in biochemical assay (Cushman et al, 2000;Antony et al, (Ross et al, 1979;Kohn, 1991 .…”
Section: Discussionmentioning
confidence: 99%
“…Although not as potent as CPT, its chemical stability, unique Top1 cleavage sequence preference, and slower cleavage complex reversibility made NSC 314622 a good lead compound. By chemically modifying NSC 314622, we synthesized indenoisoquinoline derivatives to increase Top1 inhibition and cancer cell cytotoxicity (Strumberg et al, 1999;Cushman et al, 2000;Fox et al, 2003). As reported previously , one of the derivatives MJ-III-65 (NSC 706744), with an amino alcohol instead of a methyl at the N-6 position of the parent compound ( Fig.…”
mentioning
confidence: 99%
“…NSC 314622 served as a lead compound for the development of indenoisoquinolines to overcome some of the limitations of CPTs and to develop novel classes of Top1 inhibitors with different anticancer activity profiles. We have now synthesized and tested >300 indenoisoquinoline derivatives and found that some of them are both very potent Top1 poisons and exhibit antitumor activity in mouse models (10)(11)(12)(13). We have also obtained crystal structures of two different indenoisoquinolines within Top1 cleavage complexes (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Docking Simulations The pdb file about the crystal structure of DNA-Top I bound to SA315F (PDB code: 1T8I) 28,29) was obtained from the RCSB Protein Data Bank (http://www. pdb.org).…”
Section: Methodsmentioning
confidence: 99%